Blood Cell Palmitoleate-Palmitate Ratio Is an Independent Prognostic Factor for Amyotrophic Lateral Sclerosis. - Alexandre Henriques; Hélène Blasco; Marie-Céline Fleury; Philippe Corcia; Andoni Echaniz-Laguna; Laura Robelin; Gabrielle Rudolf; Thiebault Lequeu; Martine Bergaentzle; Christian Gachet; Pierre-François Pradat; Eric Marchioni; et al. (PLoS ONE, 2015)
Growing evidence supports a link between fatty acid metabolism and amyotrophic lateral sclerosis (ALS). Here we determined the fatty acid composition of blood lipids to identify markers of disease progression and survival. We enrolled 117 patients from two clinical centers and 48 of these were age and gender matched with healthy volunteers. We extracted total lipids from serum and blood cells, and separated fatty acid methyl esters by gas chromatography. We measured circulating biochemical parameters indicative of the metabolic status. Association between fatty acid composition and clinical readouts was studied, including ALS functional rating scale-revised (ALSFRS-R), survival, disease duration, site of onset and body mass index. Palmitoleate (16:1) and oleate (18:1) levels, and stearoyl-CoA desaturase indices (16:1/16:0 and 18:1/18:0) significantly increased in blood cells from ALS patients compared to healthy controls. Palmitoleate levels and 16:1/16:0 ratio in blood cells, but not body mass index or leptin concentrations, negatively correlated with ALSFRS-R decline over a six-month period (p<0.05). Multivariate Cox analysis, with age, body mass index, site of onset and ALSFRS-R as covariables, showed that blood cell 16:1/16:0 ratio was an independent prognostic factor for survival (hazard ratio=0.1 per unit of ratio, 95% confidence interval=0.01-0.57, p=0.009). In patients with high 16:1/16:0 ratio, survival at blood collection was extended by 10 months, as compared to patients with low ratio. The 16:1/16:0 index is an easy-to-handle parameter that predicts survival of ALS patients independently of body mass index. It therefore deserves further validation in larger cohorts for being used to assess disease outcome and effects of disease-modifying drugs.